Father presence and resilience of Chinese adolescents in middle school: Psychological security and learning failure as mediators - Wei, Xueyan; Zhuang, Miao; Xue, Linfang (Frontiers in Psychology, 2023)
This study aimed to explore the association between father presence and adolescent resilience and the mediating role of psychological security and failure learning. Examining the mediating effects of failure learning and the chain mediating effect of psychological security and failure learning elucidated the link between father presence and adolescent resilience. The research conducted a questionnaire survey among Chinese middle school students on father presence, resilience, psychological security, and failure learning. The survey collected 626 valid responses. The findings showed that father presence, psychological security, failure learning, and resilience were significantly positively correlated; father presence had a direct effect on adolescent resilience; psychological security and failure learning both mediated the relation between father presence and adolescent resilience; psychological security and failure learning served as chain mediators between father presence and adolescent resilience. Meanwhile, this research hoped to contribute theorital and practical insights to the field of family education.